Medical Pharmacology and Therapeutics - Waller, Derek G.; Renwick, Andrew G.; Hillier, Keith (Saunders Elsevier, 2010)
This textbook on medical pharmacology and therapeutics provides a basis for learning about a safe and effective prescribing of modern medicines by including descriptions of the pathogenic mechanisms of the disease or condition, where and how drugs have their actions and unwanted effects, and the therapeutic principles of drug use.